A Review of Current Knowledge of Zamiaceae, With Emphasis on Zamia From South America - Segalla, Rosane [UNESP]; Telles, Francismeire Jane; Pinheiro, Fábio; Morellato, Patrícia [UNESP] (SAGE Publications, 2019)
Zamiaceae, a family of the ancient order Cycadales, is distributed throughout the tropical and subtropical regions of both the Old and New Worlds. Here, we present a systematic review of Zamiaceae with emphasis on Zamia species from South America. We aim to (a) establish the current knowledge, (b) identify research gaps, and (c) indicate directions for future studies, discussing ecology and conservation of South America species. The search recovered 508 papers, further classified into 11 research topics: taxonomy and systematics, morphology, biochemistry, genetics, phylogeography, population ecology, reproductive biology, ecological interactions, plant propagation, conservation, and reviews. The number of publications doubled in the 21st century, mostly focusing on genetics (n = 60), taxonomy and systematics (n = 52), morphology (n = 36), ecological interactions (n = 30), and an increasing interest in population ecology (n = 29) and conservation (n = 32). Studies are concentrated in North and Central America (54% of all studies) with just 6% (29) addressing South America species of Zamia. Overall, studies point out the key role of pollinators in promoting gene flow through pollen dispersal among populations of Zamiaceae. Therefore, investigate natural history, ecology, reproductive biology, genetic, and phylogeography, especially for South America species, are needed. Moreover, the implementation of in situ and ex situ collections and germplasm banks linked to botanical gardens are essential for the conservation and reestablishment of local populations of critically endangered Zamia species in South America. Concomitantly, we suggest studies modeling the distribution of Zamia species in future climate change scenarios.
Keywords: cycad conservation; ecological interactions; phylogeography; reproductive system; seed dispersal